2016
DOI: 10.1242/bio.018903
|View full text |Cite
|
Sign up to set email alerts
|

Strategies used by two apterous strains of the pea aphid Acyrthosiphon pisum for passive dispersal

Abstract: Wingless forms of aphids are relatively sedentary, and have a limited ability to migrate or disperse. However, they can drop off hosts or walk away if disturbed, or their food quality or quantity become deteriorated. Earlier, we found that the pea aphid, Acyrthosiphon pisum (Harris, 1776), could use differed strategies to escape danger and locate new host plants. To determine the mechanisms behind the different strategies, we undertook a series of studies including the aphids' host location, energy reserves un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…In turn, greater A. pisum per capita reproduction led to an increased proportion of individuals off of source plants, an indicator of increased plant-to-plant movement. Prior studies show that when A. pisum individuals reach high densities on plants, crowding can exacerbate plant-to-plant movement or alate production [44,45]. Disease ecology models show that the prevalence of persistent pathogens can increase in response to density-dependent movement [46] or when vectors increase plant-to-plant movement in response to interactions with competitors [47].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, greater A. pisum per capita reproduction led to an increased proportion of individuals off of source plants, an indicator of increased plant-to-plant movement. Prior studies show that when A. pisum individuals reach high densities on plants, crowding can exacerbate plant-to-plant movement or alate production [44,45]. Disease ecology models show that the prevalence of persistent pathogens can increase in response to density-dependent movement [46] or when vectors increase plant-to-plant movement in response to interactions with competitors [47].…”
Section: Discussionmentioning
confidence: 99%
“…The body-color polyphenism (red and green) may be related to carotenoids composition rather than the level of total carotenoids content (Moran and Jarvik, 2010; Tsuchida, 2016). The differences of total carotenoids in the two-color forms of A. pisum are probably associated with biological and ecological adaptations, such as host location, energy reserves, and probing behavior (Tsuchida, 2016; Zhang et al, 2016), which will require further study.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of CdeB prolonged nymph development duration in the present generation, altered the body weight and age structure, and significantly decreased the total aphid population number. Several studies have suggested that the red pigment could be used as a backup energy source that influences body length, body weight, finding of new hosts, and starvation resistance …”
Section: Discussionmentioning
confidence: 99%